Fuel Subsidy Removal and Household Expenditures in Obajana Kingdom of Kogi State, Nigeria - Audu, Bello; Ilevbare, Igheoise Trust; Yusufu, Ahmed Audu (Kashere Journal of Politics and International Relations, 2024)
This article endeavours to accomplish three primary objectives: firstly, to assess the impact of the 2023 removal of fuel subsidies on household expenditures within Obajana Kingdom; secondly, to explore the coping mechanisms adopted by households to mitigate resultant economic pressures; and thirdly, to analyse individual perceptions regarding the subsidy removal. The article adopts a mixed-method approach, employing structured questionnaires and Key Informant Interviews (KIIs) for primary data collection, and secondary data from scholarly literature and peer-reviewed journals. The theoretical framework guiding the study draws from the Microeconomics theory of Consumer Behaviour. Quantitative data from the questionnaires underwent descriptive analysis, while qualitative data from KIIs were content-analyzed, revealing a significant rise in household spending on essential goods like food, housing, transportation, healthcare, and education following the subsidy removal. Household coping strategies include intensified efforts to secure employment and generate income, increased reliance on credit, reduced savings, transition from gas to firewood for cooking, adoption of cost-effective alternatives for food and household items, and decreased use of private transportation. A predominant sentiment among respondents was negative toward the subsidy removal. Based on these findings, the study recommends several policy interventions. These include the implementation of government subsidies for food and public transportation, strengthening consumer protection laws to counter exploitative pricing, initiatives to tackle housing affordability issues, and support for the agricultural sector to stabilize food prices.